Recovery of Hippocampal-Dependent Learning Despite Blunting Reactive Adult Neurogenesis After Alcohol Dependence - Nickell, Chelsea G. (Brain Plast, 2020)
BACKGROUND: The excessive alcohol drinking that occurs in alcohol use disorder (AUD) causes neurodegeneration in regions such as the hippocampus, though recovery may occur after a period of abstinence. Mechanisms of recovery are not clear, though reactive neurogenesis has been observed in the hippocampal dentate gyrus following alcohol dependence and correlates to recovery of granule cell number. OBJECTIVE: We investigated the role of neurons born during reactive neurogenesis in the recovery of hippocampal learning behavior after 4-day binge alcohol exposure, a model of an AUD. We hypothesized that reducing reactive neurogenesis would impair functional recovery. METHODS: Adult male rats were subjected to 4-day binge alcohol exposure and two approaches were tested to blunt reactive adult neurogenesis, acute doses of alcohol or the chemotherapy drug, temozolomide (TMZ). RESULTS: Acute 5 g/kg doses of EtOH gavaged T6 and T7 days post binge did not inhibit significantly the number of Bromodeoxyuridine-positive (BrdU+) proliferating cells in EtOH animals receiving 5 g/kg EtOH versus controls. A single cycle of TMZ inhibited reactive proliferation (BrdU+ cells) and neurogenesis (NeuroD+ cells) to that of controls. However, despite this blunting of reactive neurogenesis to basal levels, EtOH-TMZ rats were not impaired in their recovery of acquisition of the Morris water maze (MWM), learning similarly to all other groups 35 days after 4-day binge exposure. CONCLUSIONS: These studies show that TMZ is effective in decreasing reactive proliferation/neurogenesis following 4-day binge EtOH exposure, and baseline levels of adult neurogenesis are sufficient to allow recovery of hippocampal function.